2020
DOI: 10.1002/jbm.a.36978
|View full text |Cite
|
Sign up to set email alerts
|

The role of macrophages in osseointegration of dental implants: An experimental study in vivo

Abstract: To investigate the role of macrophages in the osseointegration of dental implants through induced macrophage reduction in a murine model. Fifty‐four Sprague–Dawley rats with bilateral maxillary first molars replaced by titanium implants were randomly assigned into three groups. For the test group, macrophages were depleted by tail‐vein injection of clodronate liposome (20 mg/kg) 3 days before implantation and reinjection every 3 days until the sacrifice of the rats (10 mg/kg). Animals treated with Phosphate Bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 47 publications
1
23
0
Order By: Relevance
“…In the case of one‐time CL injection, macrophages appear again about 4 days after the administration; this is consistent with findings from previous studies 35‐37 . Furthermore, repeated CL injection was considered in several reports 32,37 .…”
Section: Discussionsupporting
confidence: 89%
“…In the case of one‐time CL injection, macrophages appear again about 4 days after the administration; this is consistent with findings from previous studies 35‐37 . Furthermore, repeated CL injection was considered in several reports 32,37 .…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, inflammatory cells and giant cells associated with barrier membranes were recognized as a compromised healing sign [ 62 ]. While the exact mechanism of macrophage polarization and interaction with biomaterials remains unclear, recent studies have suggested that macrophages might have no deleterious effect on final formation of osseointegration [ 63 , 64 , 65 ] and that inflammatory infiltration were not able to inhibit bone regeneration [ 5 , 60 , 66 ]. Since this present study was limited to the biologic response of the implanted membranes incorporated with antibiofilm, further work that addresses functionality in promoting bone regeneration will be conducted before extrapolating to more statements in that direction.…”
Section: Discussionmentioning
confidence: 99%
“…It has been postulated that monocytic-derived cells, possibly osteomacs, arrive at the titanium implant surface differentiating into pro-regenerative M2 and then recruiting osteoprogenitor cells to build the peri-implant new bone [ 57 ]. In fact, a macrophage depleted model showed both a reduced number of osteoblasts and less bone formation around implants [ 58 ].…”
Section: Immunity: a Pivotal Player To Achieve And Maintain Osseointementioning
confidence: 99%